2007
DOI: 10.1182/blood-2006-08-036947
|View full text |Cite
|
Sign up to set email alerts
|

Extended follow-up of a phase 3 trial in relapsed multiple myeloma: final time-to-event results of the APEX trial

Abstract: myeloma patients showed significantly longer time to progression, higher response rate, and improved survival with single-agent bortezomib versus high-dose dexamethasone. In this updated analysis (median follow-up: 22 months), survival was assessed in both arms, and efficacy updated for the bortezomib arm. Median survival was 29.8 months for bortezomib versus 23.7 months for dexamethasone, a 6-month benefit, despite substantial crossover from dexamethasone to bortezomib. Overall and complete response rates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
384
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 503 publications
(407 citation statements)
references
References 23 publications
17
384
2
4
Order By: Relevance
“…The higher response rates observed in this study were similar as previous studies [8,20]. The APEX study showed that patients receiving bortezomib earlier have higher response rates and longer survival [15]. Additionally, this study had a rapid response to bortezomib-based treatment, after a median time of 22 days, namely the first cycle of treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The higher response rates observed in this study were similar as previous studies [8,20]. The APEX study showed that patients receiving bortezomib earlier have higher response rates and longer survival [15]. Additionally, this study had a rapid response to bortezomib-based treatment, after a median time of 22 days, namely the first cycle of treatment.…”
Section: Discussionsupporting
confidence: 89%
“…The activity and safety of bortezomib in MM has been clearly demonstrated in several large multicenter studies [13][14][15]. Based in part on data from the SUMMIT [13] and CREST [14] studies, single-agent bortezomib was approved at 1.3 mg/m 2 twice weekly every 3 weeks for the treatment of MM in patients who have received at least one prior therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although a confirmed partial response or better was observed in only 17.4% of the patients, most of these patients were heavily pretreated and refractory to prior therapies. In addition, the median TTP observed in this study (7.9 months) was slightly longer than that reported in patients treated with bortezomib as a single agent (6.2-7.0 months) [3,15].…”
Section: Discussioncontrasting
confidence: 62%
“…Even after initial response to treatment, nearly all multiple myeloma patients eventually relapse or become refractory to treatment [2]. Median survival of patients with relapsed multiple myeloma treated with bortezomib in the Assessment of Proteasome Inhibition for Extending Remissions (APEX) trial was 29.8 months [3]; however, survival of such patients declines after each subsequent regimen [4]. A significant unmet medical need remains, and new agents are needed for the treatment of patients with multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation